Hubungan Asupan Fe dan Kualitas Tidur dengan Kejadian Anemia pada Remaja Putri di SMAN 2 Wawotobi Kabupaten Konawe - Kalsum, Umi; Mayangsari, Riska; Demmalewa, Jenny Qlifianti (Jurnal Gizi Ilmiah, 2023)
Anemia is the most common nutritional problem throughout the world, especially in developing countries. Surveys from various countries show that the prevalence of anemia ranges from 32% -55%. This study aims to understand the relationship between Fe consumption and sleep quality with the incidence of anemia in adolescent girls at Wawotobi 2 Public High School Konawe District. The study was conducted with a cross sectional design with a quantitative approach, there were 32 samples. The sampling technique uses saturated samples. The results of this study indicate that there is no relationship between Fe consumption with the incidence of anemia in adolescents in Wawotobi 2 High School with a p value of r=-0,313 and there is no relationship between sleep quality with the incidence of anemia in adolescent girls in Wawotobi 2 High School with a value of p value 0,102 ˂α (0,05).